2021
DOI: 10.1093/bjsw/bcab247
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Theory of Moral Distress in Child Welfare Workers

Abstract: Child welfare (CW) professionals who provide direct services to families, referred to as ‘caseworkers’ in the USA, often have to act in ways that are inconsistent with their professional values, leading to feelings of guilt, anxiety and self-blame, referred to as moral distress. The conceptual basis for moral distress primarily comes from the nursing literature, leaving a theoretical gap in how CW workers experience moral distress. Hence, this study used qualitative system dynamics modelling to develop a dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We do well to recall the survey respondent who considered that the system made child protection workers operate contrary to how they preferred to operate. The literature tends to support this view (Krumer-Nevo, 2020;Lonne et al, 2013;Marsh et al, 2015;Stahlschmidt et al, 2022). Through supporting and learning new child protection practices from Aboriginal third parties, the beliefs underpinning the edifice of child protection may be challenged sufficiently to make way for a relational care ethic to take hold to benefit everyone.…”
Section: Discussionmentioning
confidence: 99%
“…We do well to recall the survey respondent who considered that the system made child protection workers operate contrary to how they preferred to operate. The literature tends to support this view (Krumer-Nevo, 2020;Lonne et al, 2013;Marsh et al, 2015;Stahlschmidt et al, 2022). Through supporting and learning new child protection practices from Aboriginal third parties, the beliefs underpinning the edifice of child protection may be challenged sufficiently to make way for a relational care ethic to take hold to benefit everyone.…”
Section: Discussionmentioning
confidence: 99%
“…Child welfare workers regularly work around the clock and for agencies that often face difficulties in obtaining resources (Beer, Phillips, Letson, & Wolf, 2021;Kim, Ji, & Kao, 2011). Also, research has identified that case severity, public perception, moral distress, and amount of time needed to spend with clients all contribute to stress (Kothari et al, 2021;Lawrence, Zeitlin, Auerbach, Chakravarty, & Rienks, 2018;Stahlschmidt, He, & Lizano, 2021;Zeitlin, Chakravarty, Lawrence, & DeCristofano, 2019). While the body of the literature examining factors that contribute to stress in child welfare is robust, a meta-analysis by Kim and Kao (2014) categorized all relevant factors leading to turnover into four domains including demographic predictors, work-related predictors, work environment, and attitudes/perceptions.…”
Section: Occupational Stress In Child Welfarementioning
confidence: 99%